Generation of a hiPSC line (TONGJIi001-A) from a 46,XX,ins(1;15)(p13.3; q22.31q26.1),inv(2)(p22.1p16.3),t(2;14)(q34;q12) infertility patient - Yunzhe Kang; Shanshan Liang; Shaorong Gao; Jiayu Chen (Stem Cell Research)
We have successfully derived a hiPSC line from PBMCs obtained from a 41-year-old infertile female. The patient’s karyotype, as determined by Bionano OGM, revealed complex chromosomal rearrangements, including 46,XX,ins(1;15)(p13.3;q22.31q26.1),inv(2)(p22.1p16.3),t(2;14)(q34;q12). Specifically, the episomal plasmids encoding key reprogramming factors OCT4, sh-p53, SOX2, KLF4, L-MYC, and LIN28 were applied to generate the integration-free hiPSC line, which was designated as TONGJIi001-A. This line exhibits typical hiPSC morphology, expresses core pluripotency markers and presents the ability to differentiate into all three germ layers in vitro. Collectively, hiPSC TONGJIi001-A provides a valuable resource for investigating the mechanisms underlying chromosomal structural abnormalities associated with infertility.